Timol, um monoterpeno, protege camundongos submetidos a isquemia cerebral focal permanente contra déficit de memória e dano neuronal - Parente, Ana Caroline Barros (2024)
Stroke (Cerebrovascular Accident - CVA) is the second leading cause of death and disability worldwide and involves the reduction of blood supply to brain areas. In Brazil, stroke is the leading cause of disability in people over 50 years old due to its high morbidity and mortality, generating high costs for treatment and rehabilitation. Stroke results in excitotoxicity, oxidative stress, apoptosis, and tissue damage in the affected region. Thymol, a monoterpene found in aromatic plants, has antimicrobial, antifungal, antitumor, antibacterial, and anti-inflammatory activities. We aim to evaluate the effects of thymol on neuronal damage, memory deficits, oxidative stress, and acetylcholinesterase activity in mice subjected to permanent focal cerebral ischemia (pMCAO). Male Swiss mice were used, divided into five groups: FO, FO+THYMOL50, pMCAO, pMCAO+THYMOL25, pMCAO+THYMOL50 (orally administered). The animals received thymol three hours after pMCAO for 5 days. After treatment, the animals underwent sensorimotor, locomotor (open field), and memory (recognition, working, and aversive) evaluations. The animals were euthanized, and brain areas (temporal cortex, striatum, and hippocampus) were collected for the evaluation of infarct area and neuronal death (2,3,5-triphenyltetrazolium chloride (TTC) staining, cresyl violet), oxidative stress (Malondialdehyde (MDA), nitrite, and total thiols), and acetylcholinesterase activity. Treatment with thymol (50 mg/kg) protected against sensorimotor deficits and reduced the infarct area in animals subjected to pMCAO. Treatment with thymol (mg/kg) protected the animals against deficits in vertical locomotor activity. Thymol (25 mg/kg) protected the mice against working memory and late aversive memory deficits. Thymol, reduced impairment in recent and late recognition memory in mice. Thymol protected against the increase in MDA concentration in the striatum and hippocampus and against the increase in nitrite concentration in the temporal cortex and hippocampus of the animals. Treatment with thymol at a dose of 50 mg/kg was able to increase the total thiol content concentration in the striatum of the mice. Thymol (50 mg/kg) inhibited acetylcholinesterase activity in the total cortex, which was increased in the animals. Thymol, increased cell viability evaluated by cresyl violet staining in the striatum and hippocampus (CA1, CA3, and DG regions) of the mice. Our results indicate that thymol can modify several pathways associated with cerebral ischemia. These changes include the prevention of oxidative stress, improvement of cholinergic neurotransmission, mitigation of sensorimotor deficits, and neuronal loss, as well as reducing memory deficits caused by the condition. These findings suggest that thymol could be a potential therapeutic agent to attenuate the damage caused by cerebral ischemia.